Conceptualizing the Design of ERP Project Model for Postgraduate Study in Tertiary Institutions - Aroba, Oluwasegun Julius; Manduth, Ramchander; Govender, Rosaline; Jali, Lulu Fortunate (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose – This concept paper proposes a novel approach for a single Enterprise Resource Planning (ERP) system for postgraduate studies. This research aims to develop an extended Technology Acceptance Model (TAM) that considers the key aspects of ERP adoption in postgraduate universities through a comprehensive analysis of the existing literature.  The 21st century has brought forth the most effective and efficient simplification of practically every element of life, where ERP (Enterprise Resource Planning) systems come into play. Method – The study will synthesize the current initial system review approach, which was deployed with the use of an enterprise resource planning (ERP) design project model for postgraduate studies in tertiary institutions. Result and Conclusion -  It is evidenced that the TAM Model is a model that is needed within the new generational operation of postgraduate studies. It will enhance all processes in a unified form without silos of functions from different departments across the postgraduate studies. Recommendations -  Institutions should use a modular and adaptable design strategy to improve the efficacy of ERP systems designed for postgraduate study.  This makes it possible to modify the system to meet each institution's unique administrative, academic, and research needs. Research Implications -  This study on ERP implementation is less commonly used in most postgraduate studies in education, and the search in this field is still in its early stages. Although many postgraduate studies Institutions have deployed ERP solutions or are mandating ERP systems, the failure rate of ERPs within postgraduate studies institutions is significantly higher than that of other industries. Practical Implications - It became evident that computer-related variables, computer self-efficacy, and computer-related factors within the company, such as top management, are the primary categories of characteristics that have been widely examined and found to be crucial to understanding ERP adoption and acceptance.